Assessment of performance of Nitinol-based arch wedge supports in bearing forces and stresses due to human movement using FEA. Issue 5 (3rd September 2018) - Stranburg, Tyler; Liu, Yucheng; Chander, Harish; Knight, Adam
Abstract: A computational investigation was performed in this study to evaluate the force bearing and deflection performance of a nitinol-based arch wedge support (AWS) design. Effects of force, boundary condition, and thickness on the mechanical behavior of the AWS design are discussed based on the obtained numerical results. Various force conditions corresponding to five typical human movements are calculated and considered for the finite element analysis (FEA) simulations. Two extreme boundary conditions are evaluated, a fully constrained case in which the AWS model cannot move, and a less constrained case to simulate the scenario that an AWS moves along the inner surface in the rear of shoe while its bottom stays in contact with the bottom inside surface of the shoe. The two selected boundary conditions represent scenarios where most and least degrees of freedom of the AWS model are constrained, respectively. Any real boundary conditions that an AWS may be subject within the shoe can be modeled as a combination of the two motions. Three thicknesses, 1 mm, 2.5 mm, and 5 mm, are evaluated in this study to determine the thickness effects. The results confirm that the proposed thin-walled nitinol AWS design is capable of resisting various forces and motions without any permanent deformation. Since this is the first time that a thin-walled nitinol AWS design is proposed and there is no previous experimental data, mesh refinement and numerical sensitivity analysis are also conducted to make sure that the FEA results would correctly reflect the real world results. Based on the results obtained from this study, a prototype of the AWS will be developed using additive manufacturing technologies for further human factors and material testing.